ADAM-10 Regulates MMP-12 during Lipopolysaccharide-Induced Inflammatory Response in Macrophages - Yan Jiang; Qiming Gong; Jinmei Huang; Yuanxun Gong; Qiang Tang; Dalong Wei; Qianli Tang; Jingjie Zhao; Jian Song; Lingzhang Meng (Journal of Immunology Research)
A disintegrin and metalloprotease 10 (ADAM-10), a member of the ADAM protease family, has biological activities related to TNF-α activation, cell adhesion, and migration, among other functions. Macrophages are important immune cells that are involved in the inflammatory response of the body. ADAM-10 is involved in inflammatory responses, but the specific regulatory mechanisms are not fully understood. In this study, we investigated the regulatory mechanism of ADAM-10 in the lipopolysaccharide-promoted proliferation (LPS) of the macrophage inflammatory response. Differentially expressed or regulated proteins were identified in interfered ADAM-10 (sh ADAM-10) macrophages using tandem mass tag (TMT) proteomics. The changes and regulatory role of ADAM-10 during LPS-induced inflammatory response in normal, interfering, and overexpressing ADAM-10 (EX ADAM-10) cells were determined. Results indicated that ADAM-10 interference affected inflammation-related pathways and reduced matrix metalloproteinase 12 (MMP-12) protein levels, as identified by TMT proteomics. In normal cells, LPS decreased ADAM-10 gene expression, but promoted ADAM-10 secretion, MMP-12 and TNF-α gene expression, and MMP-12, iNOS, IL-10, and cyclinD1 protein expression. Additionally, ADAM-10 knockdown decreased macrophage viability in sh-ADAM-10 cells. Moreover, an MMP-12 inhibitor had no impact on the viability effect of LPS on cells or the expression of ADAM-10. iNOS expression decreased, whereas IL-10 expression increased after ADAM-10 depletion. ADAM-10 knockdown decreased MMP-12, iNOS, TNF-α, IL-1β, and FKN, while overexpression had an opposite effect. ADAM-10 overexpression further increased MMP-12, iNOS, and TNF-α gene expression in response to LPS. Cell viability was increased in EX ADAM-10 cells, and ADAM-10 secretion was further increased in the EX and LPS groups. Flow cytometry and immunofluorescence staining revealed that EX-ADAM 10 cells had increased iNOS expression, which acted as an IL-6 expression driver. In summary, we found that ADAM-10 is activated by LPS and positively participates in LPS-stimulated macrophage inflammatory responses by positively regulating MMP-12 during the inflammatory process.